Remote Actuation of Apoptosis in Liver Cancer Cells via Magneto-Mechanical Modulation of Iron Oxide Nanoparticles - Lunov, Oleg; Uzhytchak, Mariia; Smolková, Barbora; Lunova, Mariia; Jirsa, Milan; Dempsey, Nora M; Dias, André L; Bonfim, Marlio; Hof, Martin; Jurkiewicz, Piotr; Petrenko, Yuri; Kubinová, Šárka; et al. (Cancers, 2019)
Lysosome-activated apoptosis represents an alternative method of overcoming tumor resistance compared to traditional forms of treatment. Pulsed magnetic fields open a new avenue for controlled and targeted initiation of lysosomal permeabilization in cancer cells via mechanical actuation of magnetic nanomaterials. In this study we used a noninvasive tool; namely, a benchtop pulsed magnetic system, which enabled remote activation of apoptosis in liver cancer cells. The magnetic system we designed represents a platform that can be used in a wide range of biomedical applications. We show that liver cancer cells can be loaded with superparamagnetic iron oxide nanoparticles (SPIONs). SPIONs retained in lysosomal compartments can be effectively actuated with a high intensity (up to 8 T), short pulse width (~15 µs), pulsed magnetic field (PMF), resulting in lysosomal membrane permeabilization (LMP) in cancer cells. We revealed that SPION-loaded lysosomes undergo LMP by assessing an increase in the cytosolic activity of the lysosomal cathepsin B. The extent of cell death induced by LMP correlated with the accumulation of reactive oxygen species in cells. LMP was achieved for estimated forces of 700 pN and higher. Furthermore, we validated our approach on a three-dimensional cellular culture model to be able to mimic in vivo conditions. Overall, our results show that PMF treatment of SPION-loaded lysosomes can be utilized as a noninvasive tool to remotely induce apoptosis.
Keywords: apoptosis; pulsed magnetic field; lysosomal membrane permeabilization; lysosomal death pathways; magnetic nanoparticles